A diagnostic approach to the institutional analysis of climate adaptation - Christoph Oberlack; Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2013)
Economics has a key role to play for understanding vulnerability and adaptation to climate change. However, economic approaches to climate adaptation are rarely articulated and discussed at a framework level. This article first reviews and critically assesses welfare economics approaches to climate adaptation and, secondly, develops a novel institutional economics approach to climate adaptation. Concepts and tools of welfare economics have contributed to assessments of benefits and costs of adaptation; outlined strategies for adaptation; identified responsibilities of the public sector and described policy instruments for adaptation. However, the neoclassical framing of collective action based on the concept of market failure seems too narrow to do analytical justice to the multitude of governance challenges associated with adaptation. Adaptation economics seems underequipped with analytical tools to study the role of institutions for climate adaptation. Therefore, an institutional economics approach to climate adaptation is developed and illustrated. This approach contributes to integrated economic analyses of climate adaptation in three major ways: First, by broadening the scope of climate adaptation economics; second, by delivering a diagnostic framework of climate adaptation that enables the analyst to explain adaptation processes in a systematic manner, synthesizes findings from a large number of research efforts, places particular research questions, governance problems and results in a broader context, and can guide the design of theoretical and empirical inquiries of climate adaptation; third, by offering research strategies and methods for developing generalisable and valid insights in the face of pronounced heterogeneity and diversity of climate adaptation.
Keywords: Q54; B52; D02; D78; 330; Economics of Climate Adaptation; Institutional Economics; Governance of Climate Adaptation; Diagnostic Framework